2012
DOI: 10.1111/j.1365-2133.2012.10904.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczema among adults: prevalence, risk factors and relation to airway diseases. Results from a large-scale population survey in Sweden

Abstract: Eczema among adults is a common disease with more women than men having and having had eczema. Eczema is associated with other atopic diseases and with airway symptoms. Hereditary factors and exposure to gas, dust and fumes are associated with eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
88
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 46 publications
20
88
4
Order By: Relevance
“…A recent large-scale adult-population survey from Sweden found that both self-reported smoking during the year preceding the survey and a history of smoking (stopped smoking at least 1 year before the survey) were associated with current eczema [17]. These results were in agreement with a study from Taiwan [13] but not studies from Norway [12] or the UK [18].…”
Section: Discussionsupporting
confidence: 82%
“…A recent large-scale adult-population survey from Sweden found that both self-reported smoking during the year preceding the survey and a history of smoking (stopped smoking at least 1 year before the survey) were associated with current eczema [17]. These results were in agreement with a study from Taiwan [13] but not studies from Norway [12] or the UK [18].…”
Section: Discussionsupporting
confidence: 82%
“…27,28 But we little know about association between smoking and AE in children and we did not find such an association. Morales Suárez-Varela et al reported that passive smoking was a risk factor of AE, in 6-7 years old but not in 13-to-14 years old children.…”
mentioning
confidence: 58%
“…Kramer et al reported that environmental tobacco smoke could have only an adjuvant effect on AE in children genetically prone to allergies. 27,30 In another study from Turkey no association was found between smoking and AE. αBecause only patients with allergic history were taken to the statistical analysis, the number was small for the other significant risk factor (who has an allergy in the family).…”
mentioning
confidence: 99%
“…In a Danish population-based study including approximately 16,500 adults aged 30 to 89 years, the 1-year prevalence of atopic eczema was 14 percent [6]. In a in West Sweden study of approximately 30,000 individuals aged 16 to 75 years, the current eczema prevalence was 11 percent [7]. In a Danish cohort study including approximately 1300 individuals aged 28 to 30 years who had been followed-up for 15 years, 10 percent reported atopic dermatitis, but 6 percent were found to have atopic dermatitis at clinical examination [8].…”
Section: Epidemiologymentioning
confidence: 99%